PHARMACOKINETIC SIMULATION TO DETERMINE TARGET IN VITRO DRUG RELEASE PROFILE FOR RIVASTIGMINE CONTROLLED RELEASE FORMULATION - MOHAMMED ABDUL RAZACK,; Dr. G.S. PRASAD,; R. SANKAR,; Dr. JAYANARAYAN KULATHINGAL, (International Journal of Pharma and Bio Sciences, 2015)
Rivastigmine, an anti-Alzheimer’s drug, is effective in the treatment of mild to moderate dementia. Oral immediate release (IR) formulation suffers from limitation like severe GI adverse effects which may even result in treatment interruption, like vomiting, diarrhea and anorexia resulting in wide fluctuations in drug plasma levels and calling for altered frequency of dosing. Even the Novel Drug Delivery System such as transdermal formulation suffers from poor patient compliance. The present work aims at pharmacokinetic simulation to determine the required dose and target in vitro drug release profile required for the development of once a day controlled release drug delivery system (CRDDS) of Rivastigmine with a steady state maximum and minimum plasma concentrations (Css max and Css min) similar to that of a transdermal formulation with reduced frequency of dosing and GI adverse events. Using zero order and absorption models, dose and the in vitro drug release rate per hour for controlled release formulation of Rivastigmine were found to be 10.9 mg and 0.48 mg h-1 respectively. There is a rapid decline in the fluctuation index of controlled release formulations of rivastigmine, 0.73 as compared to 6.53 of IR formulation, indicating more constant plasma concentrations than the IR formulation, thereby reducing the adverse event. Based on the simulation study, the feasibility of Controlled release formulation of Rivastigmine is explored with a predetermined target in vitro release profile and dose prior to initiation of the formulation development, thereby reducing the cost and development timelines.